Transient elevation of high-sensitive troponin T after Cardioband implantation - Kreußer, Michael; Pleger, Sven Torsten; Abu Sharar, Haitham; Geis, Nicolas; Bekeredjian, Raffi; Katus, Hugo; Raake, Philip (Herz, 2019)
Background: The Cardioband system enables percutaneous surgical-like direct mitral valve annuloplasty and, thereby, repair of severe functional mitral valve regurgitation (MR) in patients with advanced systolic heart failure (HF) and dilation of the left ventricular (LV) annulus. Since the device is anchored by screws in the LV annulus, limited myocardial injury is likely to occur.Methods and results: Five patients (Society of Thoracic Surgeons score: 2.7 ± 0.7%) with severe HF (LV ejection fraction [LVEF]: 17 ± 1%; LV end-diastolic diameter [LVEDD]: 71 ± 3 mm) were treated with the Cardioband (sizes C-F) receiving 14-17 screws in the LV annulus region. Myocardial injury was monitored by measuring high-sensitive cardiac troponin T (hsTnT) levels and by echocardiography. All patients showed significant periprocedural increase in hsTnT levels. Peak hsTnT concentration was reached between day 1 and day 6 (593 ± 141 pg/ml). None of the patients showed clinical signs of myocardial infarction, ST-segment elevation, new onset of deteriorated myocardial wall motion, or new ventricular tachycardia. hsTnT levels normalized in all patients after 14 days (hsTnT on day 0: 34 ± 6 pg/ml vs. hsTnT on day 14: 36 ± 6 pg/ml; p = 0.604). This nonischemic hsTnT kinetics was compared to a sixth patient who experienced proximal damage of the left circumflex artery (LCX) and ST-segment elevation during the Cardioband procedure, followed by immediate repair of the LCX, avoiding structural damage of the LV. Conclusion: Cardioband implantation is accompanied by significant elevation of hsTnT without causing structural myocardial damage or clinical symptoms such as worsening of LV function, new-onset LV regions exhibiting reduced wall motion, or ventricular tachycardia.
First Online: 25 September 2018
Gesehen am 08.10.2019